1995
DOI: 10.1111/j.1476-5381.1995.tb16684.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and chronic fluoxetine administration on the spontaneous activity of dopaminergic neurones in the ventral tegmental area

Abstract: 1 Electrophysiological techniques were used to study the effects of fluoxetine and citalopram on the basal activity of dopaminergic neurones in the ventral tegmental area (VTA) and substantia nigra, pars compacta (SNc) of rats.2 Acute i.v. injection of fluoxetine (20-1280 ,ug kg-') caused a dose-dependent inhibition of the firing rate of VTA dopaminergic neurones, but did not affect the activity of dopaminergic cells in the SNc. Citalopram (20-1280 pg kg-', i.v.) inhibited the firing rate of dopaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 54 publications
7
79
1
Order By: Relevance
“…Although a recent study demonstrated that the majority of dorsal raphe neurons that project to the VTA are nonserotoninergic, 46 neuroanatomical studies have revealed 5-HT immunoreactive fibres in the VTA, 47 and there is evidence that the mesolimbic dopaminergic system is under the control of the 5-HT system. 48,49 Alteration of the 5-HT system alters cocaine sensitization As a psychostimulant, cocaine elicits a dose-dependent increase in motor activity in rodents. 50,51 Additionally, cocaineinduced motor effects depend on the number and duration of administrations, where repeated administrations result in increased motor responses (behavioural sensitization).…”
Section: Differential Roles Of Altered Da and 5-ht Systems On Locomotmentioning
confidence: 99%
“…Although a recent study demonstrated that the majority of dorsal raphe neurons that project to the VTA are nonserotoninergic, 46 neuroanatomical studies have revealed 5-HT immunoreactive fibres in the VTA, 47 and there is evidence that the mesolimbic dopaminergic system is under the control of the 5-HT system. 48,49 Alteration of the 5-HT system alters cocaine sensitization As a psychostimulant, cocaine elicits a dose-dependent increase in motor activity in rodents. 50,51 Additionally, cocaineinduced motor effects depend on the number and duration of administrations, where repeated administrations result in increased motor responses (behavioural sensitization).…”
Section: Differential Roles Of Altered Da and 5-ht Systems On Locomotmentioning
confidence: 99%
“…Here too, systemic administration of agonists (most commonly Ro 60-0175) at 5-HT2C receptors decreases DA efflux in the NA (Di Gobert et al, 2000;De Deurwaerdere et al, 2004) and decreases the firing rate of VTA DA neurons (Prisco et al, 1994;Prisco and Esposito, 1995;, 2000Gobert et al, 2000). The inverse agonist SB 206553 (Di Gobert et al, 2000) and the antagonists mesulergine and SB 242084 (Prisco et al, 1994; respectively) increase the firing rate of these neurons.…”
Section: Mesolimbic Pathwaymentioning
confidence: 99%
“…For example, systemic and microiontophoretic administration of the 5-HT 2C/1B agonist meta-chlorophenylpiperazine (mCPP) decreased the firing rate of VTA DA neurons; the systemic actions of mCPP were antagonized by the 5-HT 2/1A antagonist mesulergine, which alone increased firing rates of a subpopulation of these cells (Prisco et al 1994;Prisco and Esposito 1995). Although 5-HT 2C/2B/1B ligands failed to alter the firing characteristics of DA neurons in the substantia nigra (Kelland et al 1990; but see Stanford and Lacey 1996), the activity of VTA DA neurons is reported to increase following administration of the 5-HT 2C/2B antagonists SB 200646A (Ashby and Minabe 1996) or SB 206553 (Lejeune et al 1997).…”
mentioning
confidence: 99%
“…The ability of selective 5-HT 2C antagonists to affect hyperactivity induced by cocaine has not been analyzed, however, non-selective 5-HT 1/2 antagonists have been shown to enhance cocaine-induced hyperactivity (Scheel-Kruger et al 1977;Berman et al 1982;Herges and Taylor 1998; but see Reith 1990 andPeltier et al 1994). Since 5-HT 2C antagonists appear to increase the activity of a subpopulation of VTA DA neurons (Prisco et al 1994;Prisco and Esposito 1995;Ashby and Minabe 1996;Lejeune et al 1997) and 5-HT 2C agonists induce hypomotility (Lucki et al 1989;Kennett 1993;Kennett et al 1996), a 5-HT 2C antagonist would be predicted to increase the locomotor activation observed after cocaine administration. To test this hypothesis, we assessed the ability of the 5-HT 2C/2B antagonist SB 206553 (Forbes et al 1995;Kennett et al 1996) to modulate spontaneous and acute cocaine-induced locomotor activation.…”
mentioning
confidence: 99%